Сomparative analysis of wild and cultivated Lathyrus L. spp. according to their primary and secondary metabolite contents - A. E. Solovyeva; T. V. Shelenga; А. L. Shavarda; M. O. Burlyaeva (Вавиловский журнал генетики и селекции)
Species of the genus  Lathyrus L. are known as forage and medicinal plants, widely used in traditional medicine  and homeopathy. The content of protein,  essential  amino  acids and  carotene in their green  biomass  is higher  than  in other  annual  leguminous plants  traditionally  cultivated  in Russia. Until now, the requirements for the crop’s quality were reduced to a high content of protein  and dry matter in seeds  and herbage. In-depth biochemical  analysis of accessions  from the collection of plant genetic resources  will significantly improve  selection  of source materials  for breeding. Such tasks can be solved  using  gas chromatography with mass spectrometry in plant  diversity studies. In view of the above,  our goal was to analyze organic  acids, free amino  acids and secondary metabolites in green biomass  of Lathyrus to facilitate comprehensive assessment of its forage  and  pharmacological value. We analyzed 32 accessions  of Lathyrus sativus L., L. tuberosus L., L. sylvestris L., L. vernus (L.) Bernh., L. latifolius L. and  L. linifolius (Reichard) Bassler from the collection of the Vavilov Institute (VIR). The studied Lathyrus accessions had significant interspecific and intraspecific variability both in the composition (presence)  and number of the identified compounds. The analysis of plants across different years confirmed that biochemical parameters depended on weather conditions. The colder and drier conditions of 2012 contributed to the accumulation of organic acids (mean: 890 mg/100 g), free amino acids (mean: 201.59 mg/100 g), and secondary metabolites (mean: 84.14 mg/100 g). The range of variability for organic acids ranged from 140 to 2140, for free amino acids from 11.8 to 610, and for secondary metabolites from 4.4 to 224.6 mg/100  g. Grass pea accessions  with high organic acid, free amino acid and secondary metabolite contents were identified: k-900 (Colombia) for organic acids (2140, 610 and 178 mg/100  g); k-51 (Georgia) and k-959 (Afghanistan) for free amino acids (401.29 and 540.63 mg/100 g); k-893 (Eritrea) for secondary metabolites (199.39 mg/100 g), etc. They can serve as source material for the development of cultivars for different uses (forage and medicinal).